Memory-dictated dynamics of single-atom Pt on CeO2 for CO oxidation - Zhang, Zihao; Tian, Jinshu; Lu, Yubing; Yang, Shize; Jiang, Dong; Huang, Weixin; Li, Yixiao; Hong, Jiyun; Hoffman, Adam S.; Bare, Simon R.; Engelhard, Mark H.; Datye, Abhaya K.; et al. (Nature communications, 2023)
Single atoms of platinum group metals on CeO 2 represent a potential approach to lower precious metal requirements for automobile exhaust treatment catalysts. Here we show the dynamic evolution of two types of single-atom Pt (Pt 1 ) on CeO 2 , i.e., adsorbed Pt 1 in Pt/CeO 2 and square planar Pt 1 in Pt AT CeO 2 , fabricated at 500 °C and by atom-trapping method at 800 °C, respectively. Adsorbed Pt 1 in Pt/CeO 2 is mobile with the in situ formation of few-atom Pt clusters during CO oxidation, contributing to high reactivity with near-zero reaction order in CO. In contrast, square planar Pt 1 in Pt AT CeO 2 is strongly anchored to the support during CO oxidation leading to relatively low reactivity with a positive reaction order in CO. Reduction of both Pt/CeO 2 and Pt AT CeO 2 in CO transforms Pt 1 to Pt nanoparticles. However, both catalysts retain the memory of their initial Pt 1 state after reoxidative treatments, which illustrates the importance of the initial single-atom structure in practical applications. The use of single atoms of platinum group metals on CeO 2 is a promising approach to reduce precious metal requirements for automobile exhaust treatment catalysts. Here, the authors discovered that by manipulating the calcination temperatures, they could control the configuration of Pt1 on the CeO 2 surface, leading to differences in CO oxidation activity.